STANDARD OF ORGANIZATION FOR GARLIC POWDER ENRICHED WITH SELENIUM - L. M. Shilo; L. V. Pavlov; N. A. Golubkina; T. M. Seredin; E. V. Baranova; A. A. Koshevarov (Овощи России, 2019)
The requirements  for garlic powder enriched with selenium, dried by convective drying and homogenized, are established. Selenium-enriched  vegetables have special healing properties and are of interest as a source of selenium. Garlic enriched with selenium is grown in a number of countries (including the USA, Sabinsa) and produced in the form of capsules, tablets and granules  (BAA), as drugs that can protect against cardiovascular diseases and  cancer. The technical conditions of dried garlic with a high content of selenium were studied and identified. Based on these indicators, a standard has been developed «Dried garlic  with  high  content  of  selenium. Technical conditions». The standard was developed for the first time for the Russian Federation. Sodium selenate was applied to the soil  with a total dose of 75 mg / m2  For drying, garlic bulbs in biological ripeness, standard and non-standard, without damage by diseases and pests were used. Cloves were peeled, ground, and dried in a drying cabinet at a temperature of 70°C to constant weight. The resulting material was homogenized, the powder was stored in tightly sealed plastic bags.